2018
DOI: 10.1111/inr.12490
|View full text |Cite
|
Sign up to set email alerts
|

Family presence during resuscitation in emergency departments: professionals’ attitudes in Brazil

Abstract: Aim The study explored the views and attitudes of nurses and physicians on family presence during resuscitation in emergency departments in Brazil. Background International emergency associations endorse family presence during resuscitation; however, the extent to which it is practiced remains unclear, particularly in the Brazilian context. Research of emergency staff views and attitudes towards this practice is desirable so that actions can be identified to support families at the bedside. Methods A qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
9
1
1
Order By: Relevance
“…While the participants in our study demonstrated a moderate level of positive attitude (3.10) towards FPDR and their negative attitude (2.24) was quite lower compared with the previous reports (Cha, 2018; Lai et al, 2017), a qualitative study on FPDR among 32 physicians and nurses in two emergency departments in Brazil reported that many participants believed that family‐centred care is difficult to implement in Brazilian healthcare settings (Barreto et al, 2018). A literature review that considered the stances of healthcare providers, as well as patients' families in 62 countries, reported that only 31% of healthcare providers had a positive attitude towards family presence (Robertis et al, 2017).…”
Section: Discussioncontrasting
confidence: 81%
“…While the participants in our study demonstrated a moderate level of positive attitude (3.10) towards FPDR and their negative attitude (2.24) was quite lower compared with the previous reports (Cha, 2018; Lai et al, 2017), a qualitative study on FPDR among 32 physicians and nurses in two emergency departments in Brazil reported that many participants believed that family‐centred care is difficult to implement in Brazilian healthcare settings (Barreto et al, 2018). A literature review that considered the stances of healthcare providers, as well as patients' families in 62 countries, reported that only 31% of healthcare providers had a positive attitude towards family presence (Robertis et al, 2017).…”
Section: Discussioncontrasting
confidence: 81%
“…The participants experienced separation of children from their families during trauma resuscitation for injuries sustained from youth violence. In a study conducted by Barreto, Marcon, et al (2018) researchers found that nurses and physicians from two emergency departments tended to ask families to wait outside during emergency care. Twibell et al (2015) found that decisions on family presence during cardiopulmonary resuscitation, near resuscitation, and unplanned cardiac procedures were made on a case-by-case basis based on the perceptions of the health care team; therefore, family presence was not occurring on a consistent basis.…”
Section: Discussionmentioning
confidence: 99%
“…bed to the bathroom, room temperature is also very important in increasing the comfort of participants, room ventilation also plays an important role in providing fresh air (Hu et al 2018), Environmental conditions also affect the sleep quality of the elderly where some elderly complain that their roommates are noisy before starting to sleep and changes in room temperature such as in the rainy season cause the elderly to often wake up at night to urinate . A good room temperature accompanied by a clean room will create comfort for the elderly in meeting the quality and quantity of sleep (Barreto 2018).…”
Section: Theme 3: Religionmentioning
confidence: 99%